Production of Bioethanol from Waste Potato - Duruyurek, Merve; Dusgun, Cihan; Gulhan, Mehmet Fuat; Selamoğlu, Zeliha (Turkish Journal of Agriculture - Food Science and Technology, 2015)
Using primary energy sources in World as fossil fuels, causes air pollution and climate change. Because of these reasons, people looking for renewable energy suppliers which has less carbondioxide and less pollution. Carbon in biofuels is producing from photosynthesis. For this, burning biofuels don‘t increase carbondioxide in atmosphere. Scientists predict that plants with high carbonhydrate and protein contents are 21. centuries biofuels. Potatoes are producing over 280 million in whole world and Turkey is 6th potato producer. Turkey produces 5250000 tonne of potatoes. Approximately 20% of potatoes are waste in Niğde. Our study aimed to produce bioethanol from Solanum tuberosum by using the yeast Saccharomyces cerevisiae. As a result renewable energy sources can be produced from natural wastes.